The Effect Of Motivation, Communication, And Work Discipline On Teacher Performance At SMAN 6 Seluma - Atharrafly, Muhammad; Irwanto, Tito; Prawitasari, Andriyani (Utami Publisher, 2026)
This study aims to examine the effect of motivation, communication, and work discipline on teacher performance at SMAN 6 Seluma. Teacher performance is an important factor in the success of education. Factors such as work motivation, effective communication, and discipline are of primary concern because they are considered to have a significant effect on teacher performance. This study was conducted to determine the partial and simultaneous effects of these three variables in improving the quality of teacher performance at the school. This study uses a quantitative approach with descriptive methods and total sampling techniques from a population of 31 teachers at SMAN 6 Seluma. Data were collected through questionnaires with valid and reliable instruments analyzed using multiple linear regression with the help of SPSS 25 to test the influence of motivation, communication, and work discipline on teacher performance. The analysis results show that partially, work motivation has a positive and significant effect on teacher performance with t-count of 2.650 and a significance of 0.013, but this relationship is negative, indicating that increasing motivation may require a more in-depth evaluation of the form and source of motivation applied. Effective communication also has a positive and significant effect with t-count of 3.109 and a significance of 0.004, indicating that good communication can improve coordination and teacher performance. Work discipline shows the greatest positive effect on teacher performance, with t-count of 5.439 and a significance of 0.000. Simultaneously, the variables of motivation, communication, and work discipline have a significant effect on teacher performance with a calculated F count of 36.541 and significance of 0.000, as well as a coefficient of determination R2 of 0.780. These results confirm that these three variables collectively play an important role in improving teacher performance in schools.